2016
DOI: 10.1002/pd.4766
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing in the general obstetric population: clinical performance and counseling considerations in over 85 000 cases

Abstract: ObjectiveThe primary goal of this study was to provide clinically relevant information for appropriate patient counseling.MethodDemographics and test metrics were reviewed for 86 658 clinical cases. Outcome information was requested for samples reported as aneuploidy detected or suspected for chromosomes 21, 18, or 13; voluntary outcome reporting was encouraged for all discordant outcomes.ResultsOf 86 658 cases, 85 298 (98.4%) met inclusion criteria for result reporting. Of the 1360 (1.6%) cancellations, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 27 publications
11
71
2
1
Order By: Relevance
“…This has opened the door for serious discussion about offering NIPT as a primary pregnancy screen to all women. Our recent clinical experience publication showed that most women choosing NIPT were at less than 23 weeks gestation [24]. The lategestation samples described here performed similarly with regards to screen positive result, turnaround time, and cancelation rate to the recent all-gestational age cohort study [24].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This has opened the door for serious discussion about offering NIPT as a primary pregnancy screen to all women. Our recent clinical experience publication showed that most women choosing NIPT were at less than 23 weeks gestation [24]. The lategestation samples described here performed similarly with regards to screen positive result, turnaround time, and cancelation rate to the recent all-gestational age cohort study [24].…”
Section: Discussionmentioning
confidence: 55%
“…Our recent clinical experience publication showed that most women choosing NIPT were at less than 23 weeks gestation [24]. The lategestation samples described here performed similarly with regards to screen positive result, turnaround time, and cancelation rate to the recent all-gestational age cohort study [24]. All patients with high-risk indications should receive appropriate counseling and be offered confirmatory diagnostic testing, regardless of gestational age.…”
Section: Discussionmentioning
confidence: 95%
“…Of these, 43 cases (0.7%) did not receive a result because of laboratory technical issues: 33 (0.5%) because of interfering substance and 10 cases (0.2%) because of insufficient DNA. In a recent update from the same laboratory on 86 658 cases, only 101 patients (0.1%) did not obtain a result because of laboratory technical issues . It is of note that among the failed cases there were no aneuploidies detected.…”
Section: Resultsmentioning
confidence: 99%
“…Reports from reference laboratories have been broadly consistent with the estimates of detection rates (DRs) and false-positive rates (FPRs) established in these trials [2][3][4][5][6]. Additionally, both proof of principle [7][8][9] and data from reference laboratories [10,11] have indicated that screening is possible for select sets of microdeletion syndromes.…”
Section: Introductionmentioning
confidence: 50%